Salivary Metabolomics in Patients with Long COVID-19 Infection - Machado, Luiz [UNESP]; Prudente, Robson [UNESP]; Franco, Estefânia [UNESP]; Gatto, Mariana [UNESP]; Mota, Gustavo [UNESP]; Pagan, Luana [UNESP]; Brizola, Luís [UNESP]; dos Santos, Maércio [UNESP]; Cunha, Thulio; Sabino-Silva, Robinson; Goulart, Luiz; Martins, Mario; et al. (MDPI, 2024)
Background: Long COVID-19 has been characterized by the presence of symptoms lasting longer than 4 weeks after the acute infection. The pathophysiology of clinical manifestations still lacks knowledge. Objective: The objective of this paper was to evaluate metabolite abundance in the saliva of long COVID patients 60 days after hospital discharge. Methods: A convenience sample was composed of 30 post-discharge patients with long COVID and seven non-COVID-19 controls. All COVID-19 patients were evaluated by demographic characteristics, spirometry, 6 min walk test (6mWT), Saint George Respiratory Questionnaire (SGRQ), and body composition. Metabolomics was performed on saliva. Results: The long COVID-19 patients were 60.4 ± 14.3 years-old, and 66% male. Their lean body mass was 30.7 ± 7.3 kg and fat mass, 34.4 ± 13.7 kg. Spirometry evaluation showed forced vital capacity (FVC) of 3.84 ± 0.97 L with 96.0 ± 14.0% of the predicted value, and forced expiratory volume in the first second (FEV1) of 3.11 ± 0.83 L with 98.0 ± 16.0 of the predicted value. The long COVID-19 patients had reduced maximal inspiratory (90.1 ± 31.6 cmH2O) and maximal expiratory (97.3 ± 31.0 cmH2O) pressures. SGRQ showed domain symptoms of 32.3 ± 15.2, domain activities of 41.9 ± 25.6, and domain impact 13.7 ± 11.4, with a mean of 24.3 ± 14.9%. Physical capacity measured by distance covered in the 6mWT was 418.2 ± 130 m with a 73.3% (22.3–98.1) predictive value. The control group consisted of 44.1 ± 10.7-year-old men with a body mass index of 26.5 ± 1.66 Kg/m2. Metabolomics revealed 19 differentially expressed metabolites; expression was lower in 16 metabolites, and 2 metabolites were absent in the COVID-19 patients compared to controls. Calenduloside G methyl ester (p = 0.03), Gly Pro Lys (p = 0.0001), and creatine (p = 0.0001) expressions were lower in patients than controls. Conclusions: Long COVID-19 patients present less abundance of calenduloside G methyl ester, Gly Pro Lys, and creatine in saliva than healthy controls. Lower creatine abundance may be related to reduced physical capacity and fatigue
Keywords: COVID-19; functional capacity; metabolomics; post-COVID-19